FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN UNTUK MENERUSKAN PENDIDIKAN KE PERGURUAN TINGGI (Studi kasus pada STIE Galileo) - hendriati, yossi (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2017)
This research has a goal to analyze factors that influences employees decicion toward continuing higher education. Sample size was 100 respondent, taken with purposive sampling method, through survey. In this research, analyzing technique will be conducted by using multiple linear regression analysis.The result of this research find out several points, namely; for first hypothesis; motivation has significantly impact toward continuing higher education,, accepted. Itâs proven by the significance level of motivation at 0.002. And for the result of secondary hypothesis; standarded learning process has significantly impact toward continuing higher education, accepted. Itâs proven by the significance level of standarded learning process at 0.005. and for third hypothesis; marketing Â has significantly impact toward continuing higher education accepted, Â because it had significance level at 0.000.Key words : decision, motivation, standarded learning process, marketing.